MEKANISME CEDERA REPERFUSI - Hamzah Muhammad Zein (HUMAN CARE JOURNAL, 2021)
A reperfusion injury, also known as an ischemic reperfusion injury or a reoxygenation injury, is tissue damage caused when blood flow returns to the tissues, after a period of ischemia or oxygen deprivation (anoxia or hypoxia). One of the most common reperfusion injuries is the heart. When blood flow to the coronary circulation is compromised, myocardial ischemia and eventually cell death occur. When reperfused, it accelerates the necrotic process of myocytes, which undergo irreversible, cell swelling. In addition, the electrophysiological changes of the heart, thus manifesting arrhythmias